Evaluation of killed Aeromonas hydrophila whole cell vaccine against acute infectious abdominal dropsy in Indian major carps - Shome, Rajeshwari; Shome, B R (Indian Journal of Fisheries, 2011)
A whole cell vaccine was prepared by using a formalin killed highly virulent strainof Aeromonas hydrophila isolated from Indian major carps suffering from acuteinfectious abdominal dropsy in Andaman. Ten numbers each of Cirrhinus mrigala,Catla catla and cat fishes were vaccinated by intraperitoneal (I/P) injection andimmersion bath. Four weeks after vaccination, the efficacy was tested bychallenging with virulent strain of A. hydrophila @ 1.5 x 109/0.2ml/fish by I/P. Therelative percentage of survivability (RPS) was observed at 100, 75 and 60 in 1/P vaccinated group against 45, 25 and 20 in immersion group respectively. Strongagglutinating and precipitating antibodies were present in I/P vaccinated groupin contrast to mild delayed type reaction in immersion bath vaccinated group.However, wide range of individual variation in both the agglutinating andprecipitating antibodies was observed. Microscopic observation of blood cells fromvaccinated and control groups and the primary antigen-antibody reactionsindicated that both cellular and humoral antibodies are involved in protection, andeven the detectable level of agglutinating as well as precipitating antibodies areenough for protection. Since I/P vaccination in fish population is not a feasibleproposition, a live attenuated vaccine for use either as immersion or in the formof biofilms is urgently required